Implication : an ecocritical dictionary for art history - Braddock, Alan C., 1961- (Yale University Press, 2023)
Ecocriticism is an interdisciplinary mode of inquiry that examines the environmental significance of art, literature, and other creative endeavors.... Alan C. Braddock, a pioneer in art historical ecocriticism, presents a fascinating group of key terms and case studies to demonstrate that all art is ecological in its interconnectedness with the world.